Subdural empyema as a complication of odontogenic sinusitis: A case report (Research, Society and Development, 2023)
Odontogenic sinusitis represents between 10 and 40% of all cases of sinusitis in the population and may present with common symptoms such as nasal obstruction, anterior or posterior rhinorrhea, facial pain or pressure; and hypo- or anosmia. Although uncommon, intracranial and systemic suppurative complications have been previously reported in the literature and include brain abscess, epidural abscess and subdural empyema, associated with almost 100% morbidity and mortality, however, they are commonly related to meningitis, otogenic diseases and other sinus diseases. The aim of this study was to report a clinical case of intracranial subdural empyema associated with odontogenic infection in a previously healthy 17-year-old patient. This case highlighted the possibility of relevant complications, including even the patient's death, due to odontogenic sinusitis. Therefore, early dental planning and approach in a hospital environment are relevant and essential both in prevention and in the course of treatment, substantiating the multidisciplinary approach.